THE ROLE OF COMMUNICATION AND MARKETING STRATEGY IN REALIZING THE EDUCATIONAL MISSION - Tasya Salsabiila; Syahputra Syahputra (Business Journal : Jurnal Bisnis Dan Sosial, 2023)
Kazeto Putra Perkasa Foundation is an educational institution committed to providing a positive impact on society through educational programs and humanitarian assistance. To realize a mission that originates from the vision of the Kazeto Putra Perkasa Foundation itself, this journal was created to find out the role of communication and marketing strategies used by the Kazeto Putra Perkasa Foundation in the current competitive era. Develop strong marketing, innovative social media tactics, and strategies to build strong relationships with stakeholders, including foundation partners. In addition, this journal discusses concrete actions taken during the process of realizing the educational mission of the Kazeto Putra Perkasa Foundation, as well as the results achieved in improving the perception of the foundation and gaining support from various parties. The purpose of this research is to describe the role of communication and marketing strategies used by the Kazeto Putra Perkasa Foundation in promoting its educational services to the community. The method used in this research is qualitative descriptive research, which illustrates and describes an event that occurred. In collecting data, interviews and literature studies are the methods used to complete the theory and concepts in this research. This integrated approach has enabled the Kazeto Putra Perkasa Foundation to strengthen its position as a driver of significant change in improving social welfare and education, having a greater impact on communities in need.